Storage Allocation In Finished Goods Warehouse (Case Study Of Sock Industry In Bandung) - Anggraeni, Nitta Fitria; Maharani, Dilla Ayu; Sihombing, Kristina; Prayogi, Gustian Adhitya; Hartati, Verani (International Journal of Psychosocial Rehabilitation, 2020)
Warehouse is a temporary storage of goods, such as raw materials, work in progress or finished goods. The warehouse has a different cycle time for each item stored. All the problem that arises in warehouse such as stacking of goods, improper allocation of storage, and time for picker to collect goods. PT SCN is a company that engaged in the production and distribution of fashion products. The high level of production in this company has resulted in the unorganized storage of warehouse storage. Allocation storage of goods in warehouses must be considered carefully so as not to reduce the quality of the goods stored. Based on these problems, the purpose of this research is to be a problem solving of storage allocation. These problems can be solved by using class-based (ABC) method and First In First Out (FIFO) method. This research uses monthly demand data to get categories and avoid inventory buildup. The results of this research are the arrangement of goods in the forward area and block stage based on the capacity along with the specified categories.